Mobility Management in small and medium cities: The case of Serres - Apostolos Giantsidis (European Regional Science Association (ERSA), 2014)
Mobility Management refers to the policies and soft measures for the achievement of a more sustainable and efficient transportation system. During the last few years, many cities and even regions have started implementing transportation policies based on Mobility Management for the modification of the transportation system and the benefits from the use of the alternative means of transport (alternately: in order to modify their transportation system and to benefit from alternative means of transport). Serres is a small city in the northern part of Greece that has also undertaken Mobility Management measures, aiming to promote cycling and hence modify the travel behavior of its citizens and the image of the city. To this purpose, Serres took part in the EU program PIMMS TRANSFER. This program intends to promote cooperation between European cities and the exchange of good practices in the transportation system. To pursue the program's objective, the city of Serres built new infrastructure, set special storage places for bicycles, distributed bicycles for one year to the employees of the Municipality and the entrepreneurs of the city, developed educational events for the right usage and the proper maintenance of the bicycles and, promoted the usage of bicycles through brochures and leaflets to the entrepreneurs of the city and the employees working in the city centre. In this paper, I analyze the above quoted measures as well as complementary actions such as school events and, educational programs. Consequently, the current situation and in particular the transportation system in the city is analyzed by examining policy documents and interviews of key policy makers. Additionally, I will present future plans and strategies for further promotion of cycling and the bicycle: cycling paths, pedestrianization and parking outside the city. Finally, I will present a comparison to other European cities with similar demographic, geographic and mobility characteristics as Serres. I found that the participation of the city in the PIMMS TRANSFER program played a crucial role for the promotion of cycling. Among policy makers' actions, those with the highest impacts were from soft measures which had been taken under the guidance of the other participants, in order to let the citizens know the benefits of cycling. New infrastructure and promotional measures were quite effective, too, as the willingness of the citizens to use bicycles increased, as well as cycling for leisure activities and sports. However, cycling as a mean of commuting for daily activities is not very popular yet, because of the lack of infrastructure.
Keywords: R41; R42; 330